Intervensi Massage Aromaterapi (Lavender) terhadap Penurunan Intensitas Nyeri Penderita Neuropathy Diabetic - Rizzi Triputri Maya Meutia; Jenny Marlindawani; Kiking Ritarwan (Journal of Telenursing (JOTING), 2023)
This study aims to analyze lavender aromatherapy massage intervention to reduce pain intensity in DN patients. The method used is quantitative research with a Quasy Experimental Non-Equivalent Control Group Pretest-Postest Design. The results of this study indicate a difference between the mean value of pain intensity in the intervention group and the control group after being given treatment with the obtained value (t = -5.155, p-value = 0.000). This study concludes that lavender aromatherapy massage has a significant effect on reducing pain intensity in patients with diabetic neuropathy.